The top 100 most cited publications on astrocytes in Alzheimer’s disease from 2000 to 2025: a bibliometric analysis - He, Qi; Yu, Hong; Zhou, Xinyao; Yang, Kangyi; Xiao, Wenjie; Gao, Zirui; He, Qian (Frontiers in Neuroscience, 2025)
BackgroundThe pathogenesis of Alzheimer’s disease (AD) is closely linked to astrocytes. This study conducts a bibliometric analysis of data from a wide range of literature in this field to enhance the in-depth understanding of this area.MethodsPublications were retrieved from the 2000–2025 Web of Science Core Collection on January 21, 2025. Bibliometrix-package of R, VOSviewer and CiteSpace were used to visualize the research focus and trends.ResultsThe number of citations for the top 100 articles ranged from 208 to 602 citations, with a median of 293 and an average of 331.67 citations per article. The author with the most contributions to this collection was Holtzman David M, who authored 7 papers. Most articles originated in the United States (n = 69), while Washington University was the institution with the most cited manuscripts (n = 40). The Journal of Neuroscience contributed the most publications (n = 15), followed by Nature Neuroscience (n = 7). Co-occurrence of keywords analysis unveiled earlier studies focusing on “messenger RNA,” and “IFN-γ,” recent studies concentrated on “mechanisms,” and “activation.” Moreover, keywords burst analysis indicated that the most recent prominent keywords were “Aβ,” “activation” and “association” since 2016.ConclusionThis is the first bibliometric analysis of the top 100 cited research on astrocytes and AD from 2000 to 2025, underscoring that the United States is a prominent leader in this field. Our analysis highlighted the growing interest in the pathogenesis of astrocytes in AD. Future studies on the mechanisms underlying astrocytes in AD will facilitate further research on new therapeutic approaches.